ADAPTASI PETANI SAWAH TADAH HUJAN TERHADAP PENURUNAN PRODUKTIVITAS PADI (GAGAL PANEN) DI JORONG SUNGAI SALAK KABUPATEN TANAH DATAR - Devita Agustine; Ashaluddin Jalil (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
ricefield farmer is a farmer who manage the ricefield whose irrigation system relies heavily on rainfall.This type of rice field is only processed if there is rain water.In rain fed lowland areas it is very difficult to harvest well compared to irrigated rice fields, in rain fed rice fields most of the harvest period is only two times a year. Not infrequently, many of rainfed farmersonly can harvesting of the rice once a year and experiencing a decrease in productivity of the rice or harvesting failure. This case is the reason why the researcher want to know what is the causes of failed harvest happened in Jorong Sungai Salak,how the adaptation done by farmers in the face of harvesting failurein order to make lack of income in harvesting period doesn’t happened, then what is the efforts that have been done by the rainfed ricefield farmer in face of harvesting failure. This research use qualitative research approach and produce descriptive data. Subject is done by viewing and selecting the subject by specifying the specific characteristics landlord and cultivator farmers for the purpose of the research. The results of research indicate that the main factor causing farmers experiencing failure harvest is due to natural factors, and factors of the farmers themselves, there are three strategies are used by the farmers that are active adaptation strategy, passive and networking. The efforts that have been made in the face of harvesting failure are coming from the government and the efforts of the farmers themselves.Keywords: Adaptation, Rainfed Rice Farmers, Decreased Productivity, Failed Harvest.